2006
DOI: 10.1103/physrevb.74.205438
|View full text |Cite
|
Sign up to set email alerts
|

Theory of the Franck-Condon blockade regime

Abstract: Strong coupling of electronic and vibrational degrees of freedom entails a low-bias suppression of the current through single-molecule devices, termed Franck-Condon blockade. In the limit of slow vibrational relaxation, transport in the Franck-Condon-blockade regime proceeds via avalanches of large numbers of electrons, which are interrupted by long waiting times without electron transfer. The avalanches consist of smaller avalanches, leading to a self-similar hierarchy which terminates once the number of tran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
463
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 258 publications
(479 citation statements)
references
References 29 publications
15
463
1
Order By: Relevance
“…In the case ⌫Ͻ 0 and strong electron-ion coupling the role of cotunneling was recently studied in Ref. 31, where it was found that while it does not destroy the Franck-Condon blockade, it can dramatically affect the lowvoltage current and current noise, as well as the vibrational dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…In the case ⌫Ͻ 0 and strong electron-ion coupling the role of cotunneling was recently studied in Ref. 31, where it was found that while it does not destroy the Franck-Condon blockade, it can dramatically affect the lowvoltage current and current noise, as well as the vibrational dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the undriven [ f (t) = 0] variant of the system has been examined with regard to its transport properties. 18,[25][26][27][28] The most striking finding in this context is that of Franck-Condon blockade: strong electron-vibron interaction leads to formation of a composite state, called a polaron, which can be thought of as being made up of an electron and a "cloud" of vibrational excitations surrounding it. If the electron is to tunnel out of the quantum dot, this state has to be broken up, at an energy cost which strongly increases with the coupling, leading to an exponential suppression of tunneling.…”
Section: Modelmentioning
confidence: 99%
“…More quantitatively, we note that the factor e −λ 2 /Ω 2 matches the Franck-Condon blockade strength obtained from a classical rate equation. 18 …”
Section: A Vibron In the Ground Statementioning
confidence: 99%
See 2 more Smart Citations